1967
DOI: 10.1149/1.2426629
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hydrogen Peroxide in Oxygen Reduction at Platinum in H[sub 2]SO[sub 4] Solution

Abstract: The rotating disk electrode with a concentric ring is used to analyze the role of H2O2 in the reduction of O2 to H2O in acid solutions. No H2O2 is formed as an intermediate in the reaction path of oxygen reduction to water. Only when the residual impurities from the not sufficiently purified solutions are adsorbed at the electrode does a parallel reaction path appear in which H2O2 is formed as an intermediate that does not reduce further to H2O with any significant rate. The mechanism of O2 reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
0
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(74 citation statements)
references
References 24 publications
8
65
0
1
Order By: Relevance
“…This is in line with extensive literature for bulk Pt electrodes in acid (that goes back to Ref. [37]), indicating that the 4e À pathway is predominant in the case of the Pt(Cu) catalyst too. Fig.…”
Section: Hydrazine Oxidation In Acidsupporting
confidence: 91%
“…This is in line with extensive literature for bulk Pt electrodes in acid (that goes back to Ref. [37]), indicating that the 4e À pathway is predominant in the case of the Pt(Cu) catalyst too. Fig.…”
Section: Hydrazine Oxidation In Acidsupporting
confidence: 91%
“…Hydrogen peroxide was detected on all Pt/C samples commencing at 0.8 V. We note that the yield of H 2 O 2 increases with the decreasing platinum mass loading or site density. The lowest yield (< 2 %) is obtained with a high Pt loading approaching the results on polycrystalline platinum surface pioneered by Damjanovic et al, [65] and being the object of recent investigations for the sake of comparison with particulate platinum [55,57,66] or, as reported very recently, using scanning electrochemical microscopy. [67,68] All investigations reported so far demonstrate that hydrogen peroxide is the intermediate in the ORR process, which can be visible when the catalytic site density decreases.…”
Section: à2mentioning
confidence: 56%
“…It was found that the amount of H 2 O 2 formed is greater in alkaline than in acid media [10,12]. In alkaline solutions about 80 % of the reduction current is via the direct reduction and the remainder of the current goes to the formation of H 2 O 2 , which suggests a more complicated mechanism.…”
Section: Introductionmentioning
confidence: 99%